Measurement of the CP-violating phase ϕsand the Bs0 meson decay width difference with Bs0→ J/ψϕ decays in ATLAS - Onofre, A. (2016)
A measurement of the B-s(0) decay parameters in the B-s(0) -> J/psi/phi channel using an integrated luminosity of 14.3 fb(-1) collected by the ATLAS detector from 8TeV pp collisions at the LHC is presented. The measured parameters include the CP-violating phase phi(s), the decay width Gamma(s) and the width di ff erence between the mass eigenstates Delta Gamma(s). The values measured for the physical parameters are statistically combined with those from 4.9 fb-1 of 7TeV data, leading to the following:phi(s) = -0.090 +/- 0.078 (stat.) +/- 0.041 (syst.) radDelta Gamma s = 0.085 +/- 0.011 (stat.) +/- 0.007 (syst.) ps(-1)Gamma(s) = 0.675 +/- 0.003 (stat.) +/- 0.003 (syst:) ps(-1).In the analysis the parameter Delta Gamma(s) is constrained to be positive. Results for phi(s) and Delta Gamma(s) are also presented as 68% and 95% likelihood contours in the phi(s)-Delta Gamma(s) plane. Also measured in this decay channel are the transversity amplitudes and corresponding strong phases. All measurements are in agreement with the Standard Model predictions.